Investigation on structural, optical and photovoltaic properties of Barium doped cuprous oxide thin films by nebulizer spray technique. (4th October 2019) - Jacob, S Santhosh Kumar; Kulandaisamy, I; Valanarasu, S; Arulanantham, A M S; Ganesh, V; Shkir, Mohd; Yahia, I S
Abstract: In present work, pure and barium (Ba) doped cuprous oxide (Cu2 O) films are coated on heated glass substrate by Nebulizer spray technique (NST) by taking different doping concentration (0%, 3%, 5%, and 7%) of Ba. The XRD, AFM, optical, electrical resistivity and solar cell studies of pure and Ba doped samples were discussed. The XRD pattern confirms the polycrystalline cubic structure with a preferred (111) plane orientation. Atomic force microscopy (AFM) reveals the spherical shape nano particles. The Raman analysis confirmed the cuprous oxide phase of prepared films. The Optical analysis was revealed the decreasing in band gap with increasing barium doping concentration. The photoluminescence studies confirmed the single emission peak obtained at 630 nm for all the films corresponds to Cu2 O phase. The electrical resistivity is found to be 0.45 × 10 2 Ω cm for 7% Ba doped Cu2 O thin film and the photovoltaic properties of the fabricated solar cell i.e. FTO/n-ZnO/p-7% Ba:Cu2 O/Ag was formed for 7% Ba: Cu2 O thin film. Further, the efficiency of the fabricated solar cell is found to be 0.85%.